The Effect of Liquidity Ratio on the Company Financial Performance: Evidence from a Developing Economy - Hadi Jaaz, Adnan; Abdulhasan Jasim, Ali; Jafer Baqer, Issa; Abdullah Abbas, Yasir; Hasan Hadi, Asia (South Asian Journal of Social Sciences and Humanities, 2025)
This study purposes to analyze the link between liquidity ratios and the company financial performance of companies in developing economy. It used secondary data from 118 companies from 2020 to 2024 by using Stata data analysis software. The study found a important and positive association between liquidity ratios and company financial performance. The connection is of great significance to financial managers, investors, and policymakers, particularly in environments in the economy characterized by instability and financial variability. It was found that firms that hold moderate liquidity lacking investing professionally may smart from a lower return on investment, representative that unnecessary liquidity can be main to ineffective utilization of capital. The study suggests that firms keep a suitable balance in liquidity ratios, enough to cover short-term requests without disrupting utilization of existing funds for productive investments. Firms should grow continuing logical models to display liquidity depending on variations in the global and local economic environment to confirm high financial flexibility. The findings of this paper help financial managers make the best decisions concerning the best liquidity ratio, which balances financial safety and investment in profitable changes. Good liquidity administration increases company financial performance by decreasing financing expenses or avoiding liquidity issues.